2011
DOI: 10.1038/labinvest.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone inhibits growth of AMH type II receptor-positive human ovarian granulosa cell tumor cells by activating apoptosis

Abstract: Ovarian granulosa cell tumors (GCTs) are sex cord stromal tumors that constitute 3-5% of all ovarian cancers. GCTs usually present with an indolent course but there is a high risk of recurrence, which associates with increased mortality, and targeted treatments would be desirable. Anti-Mü llerian hormone (AMH), a key factor regulating sexual differentiation of the reproductive organs, has been implicated as a growth inhibitor in ovarian cancer. GCTs and normal granulosa cells produce AMH, but its expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 63 publications
3
36
1
1
Order By: Relevance
“…Indeed, both AMH and BMP-15 demonstrated a 3-fold augmentation of, indicating a downstream activation of the serine/threonine receptor pathway. This evidence comes in agreement with previously published data from rodents [7,11,12] and the tumor-derived human granulosa cell line KGN [54], where it has been shown that AMH activates Smad5 phosphorylation by binding to the AMHRII/-ALK2/3/6 complex, as well as, with studies in COV434 ovarian granulosa tumor cells were it has been demonstrated that BMP-15 facilitates its own effect through binding to the BMPRIB/ALK3 receptor complex and subsequently activating the Smad1/5/8 phosphorylation [55]. The fact that Smad5 is a common target for both AMH and BMP-15 in our system can explain why combined administration of these factors did not lead to an additive effect on steroids production.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, both AMH and BMP-15 demonstrated a 3-fold augmentation of, indicating a downstream activation of the serine/threonine receptor pathway. This evidence comes in agreement with previously published data from rodents [7,11,12] and the tumor-derived human granulosa cell line KGN [54], where it has been shown that AMH activates Smad5 phosphorylation by binding to the AMHRII/-ALK2/3/6 complex, as well as, with studies in COV434 ovarian granulosa tumor cells were it has been demonstrated that BMP-15 facilitates its own effect through binding to the BMPRIB/ALK3 receptor complex and subsequently activating the Smad1/5/8 phosphorylation [55]. The fact that Smad5 is a common target for both AMH and BMP-15 in our system can explain why combined administration of these factors did not lead to an additive effect on steroids production.…”
Section: Discussionsupporting
confidence: 93%
“…The previous notion that serum AMH is increased in patients with large AGCTs was confirmed in our study. Interestingly, tissue AMH expression is decreased in larger AGCTs, leading to a discrepancy with serum AMH levels. This may simply reflect the size of the tumor; larger AGCTs release more AMH into the circulation, while overall tissue expression remains low.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in vitro treatment of a human ovarian granulosa cell tumour (GCT) cell line with AMH results in inhibition of GCT through activation of the apoptosis pathway (Anttonen et al. ) could explain the self‐curing of the RO in the current report. In support of this, the histopathological examination of the current case revealed that the extracted RO contained degenerated granulosa cells in the wall of the cyst.…”
Section: Discussionmentioning
confidence: 66%